2015
DOI: 10.1155/2015/173193
|View full text |Cite
|
Sign up to set email alerts
|

Conditions to Prolonged Release of Microencapsulated Carvacrol on Alginate Films as Affected by Emulsifier Type and PH

Abstract: Alginate from algal biomass is used as edible film and the incorporation of antimicrobial agents improves its performance to increase the shelf-life of fresh foods. However, environmental conditions and intrinsic properties of films influence their release. The aim of this study was to investigate the effect of the concentration and type of encapsulating agent and pH of emulsions on the physical and antimicrobial properties of alginate-carvacrol films. Films containing alginate, carvacrol as antimicrobial agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…5b, d), demonstrating the release of the active agent in a sustained storage. Matiacevich et al (2015) previously reported the efficacy of essential oils incorporated to alginate films, who studied the antifungal activity of carvacrol against B. cinerea during storage. Results showed that B. cinerea growth was inhibited due to the prolonged release of carvacrol during storage.…”
Section: Antifungal Propertiesmentioning
confidence: 99%
“…5b, d), demonstrating the release of the active agent in a sustained storage. Matiacevich et al (2015) previously reported the efficacy of essential oils incorporated to alginate films, who studied the antifungal activity of carvacrol against B. cinerea during storage. Results showed that B. cinerea growth was inhibited due to the prolonged release of carvacrol during storage.…”
Section: Antifungal Propertiesmentioning
confidence: 99%
“…This result was attributed to the CAP characteristic of low molecular mobility by interaction with the oil component (FT‐IR Data). Previously, authors reported the lowest T 2FID values (1.5 μs) for films based on alginate and essential oil containing Capsul® (Matiacevich et al, 2015). However, when the CIT: CAP was spray‐dried, the change was insignificant ( p > 0.05), showing the relevance of the drying methodology in molecular interactions and mobility of the matrix and the importance of the structure obtained in relaxation behavior.…”
Section: Resultsmentioning
confidence: 97%
“…Slavutsky and Bertuzzi [52] reported that the terpenes present in the oil can interact with starch through weak bonds, such as hydrogen bond, guaranteeing adhesion between these materials. Carboxymethyl cellulose-agar biocomposite film with Satureja hortensise essental oil [36] and sodium alginate films with carvacrol microparticles [72] presented a greater contact angle, which is attributed to the hydrophobic nature of the added substances.…”
Section: Moisture Solubility and Contact Anglementioning
confidence: 99%